The effectiveness of Powerpoint-iSpring integrated multiple chemical representation learning media on acid-base materials to improve students learning outcomes for Senior High School - Seiski Afrita Riska; Guspatni Guspatni (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
We have previously produced a PowerPoint-iSpring Integrated Learning Media Multiple Chemical Representations on Acid-Base Materials. It is valid and practical but has not been tested for its effectiveness on student learning outcomes in Senior High School. The research is experimental with a quasi-experimental design with a Non-equivalent Control Group Design. The research population is all class XI Senior High School students for the 2021/2022 academic years. Purposive sampling was used as a sampling technique with homogeneous sampling criteria. The classes selected as samples were class XI MIPA 1 as the experimental class and class XI MIPA 2 as the control class. The instruments used were questionnaires and student learning outcomes tests in the form of 20 multiple choice questions. The N-Gain and hypothesis testing were carried out for data analysis with an independent sample t-test. Based on the data analysis, the N-Gain of the experimental class was higher than the control class with the medium category. PowerPoint-iSpring Integrated Learning Media with Multiple Chemical Representations on Acid-Base Materials is Effective for Improving Learning Outcomes of Class XI Senior High School Students.